Edukasi Dan Pelayanan Pemeriksaan Infeksi Jamur Kulit Pada Pekerja Kebersihan Universitas Di Surabaya - Anindita Riesti Retno Arimurti; Fitrotin Azizah; Dita Artanti; Rinza Rahmawati Samsudin; Yeti Eka Sispita Sari; Nur Vita Purwaningsih; Vella Rohmayani; Ellies Tunjung Sari Maulidiyanti (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Work that requires being in a humid area, can cause fungal infections. Skin fungal infections in humans can be divided into two, namely dermatophytosis and non-dermatophytosis. Dermatophytosis is a superficial fungal infection that attacks the keratinized parts of the skin, nails and hair and is caused by 3 genera, namely Microsporum, Epidermophyton, and Trichophyton. While non dermatophytosis is a fungal infection of the outer skin or this type of fungal infection does not reach the keratin tissue. Non-dermatophyte fungi include Aspergillus sp., Malessezia furfur. Due to dermatophyte and non-dermatophyte fungal infections, namely itching of the skin or earlobe. This activity aims to increase the understanding of cleaning workers at one of the universities in Surabaya about the dangers of fungus on the skin, so that they can prevent and anticipate early spread. The method used in this community service activity is the presentation and discussion of the dangers of skin fungal infections. To measure the level of understanding of the participants regarding the dangers of toxoplasmosis, a pretest was conducted at the beginning and at the end of the activity. This activity was attended by 22 janitors, both male and female. The average pretest score is 49,63 points, while the average posttest score is 71,48 points. These results indicate that there is an increase in the knowledge of cleaning workers at one of the universities in Surabaya about the causes, dangers, modes of transmission and methods of preventing skin fungal diseases. Educational activities are expected to be sustainable so that the community can apply steps to prevent skin fungal infections.